TINGKAT KEBISINGAN LALU LINTAS DI LINGKUNGAN PERUMAHAN DALUNG PERMAI KABUPATEN BADUNG - I Made Dwi Setiawan; I Gede Mahardika; I Made Adhika (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2016)
Dalung Permai housing is that has a fairly high trip generation, many had access road leading to the workplace, both working in government, private as well as to schools and shopping centers and entertainment. Ahousingshouldprovideatranquility awayfrom the noisein accordancewith the Decree of the Governor of Bali No.8 Year 2007 on Environmental Quality Standards and Criteria Raw Environmental Damage that thres hold noise level forresidential areasandsettlementsamounted to55dB.The purpose of this study was to determine the characteristics of the traffic, the noise level of traffic, the perception of the population in Dalung Permai housing. Data collected by way of interviews with respondents and direct measurements in the field. Based on the data analysis it is known that the highest traffic volume during rush hour occurred in the morning (07.00 to 09.00) in the segment Jl. Tegal Luwih with volume vehicle as much as 21.599 vehicles, the segment Jl. Dalung Permai and segments Jl. Tegal Permai occurred in the afternoon (05.00 to 07.00) with a total volume of 22.450 and 17.587 vehicles. Instantaneous speed of the average of each type of vehicle ranges between 33-40 km per hour. The main sources of traffic noise is a four-stroke motorcycles with prosenatse average reached 91.61% of the total number of vehicles. The average noise level measured has exceeded the threshold setandar quality standard that ranged from 73.71 to 76.77 dB. In the segment Jl. Tegal Luwih, segments Jl. Tegal Permai and segments Jl. Dalung Permai give the perception that the level of traffic noise in a residential area is disturbing level of comfort.